Access to Diagnostics and Treatment for People With Metastatic EGFR-Positive NSCLC: Lessons From Project PRIORITY - Jill Feldman, MA; Ivy Elkins, MBA; Zofia Piotrowska, MD; Bellinda L. King-Kallimanis, PhD; Tendai Chihuri, MD; Carly Johnson, BS; Alecia Clary, PhD; Teri Kennedy, MA; Upal Basu Roy, PhD, MPH (JTO Clinical and Research Reports)
Introduction: The treatment landscape for people diagnosed with EGFR-mutated (EGFR-m) NSCLC has rapidly evolved, yet there remains limited self-reported information about the lived experience. In this paper, we describe the clinical characteristics and treatment experiences of people living with EGFR-m lung cancer from Project PRIORITY, a patient-driven study. Methods: An online survey was distributed among the EGFR Resisters community between April 2019 and January 2020. The survey captured participants’ demographics and lung cancer risk factors, diagnostic and treatment pathways, and prevalence of side effects. Descriptive statistics were used and included subgroups based on residency and cancer stage. Results: Of the 425 participants, most were female (67%), under 60 years old (53%), and resided in the United States (74%). The most frequently reported symptom at diagnosis was cough (54%), though 18% reported no symptoms. In addition, 89% reported receiving at least one tyrosine kinase inhibitor (TKI); osimertinib was the most prescribed first-line TKI for stage IV participants diagnosed after 2017. Participants residing in the United States were more likely to have access to advanced diagnostic (next-generating sequencing) and newer treatments such as osimertinib. Just under half of the sample (47%) had experienced progressive disease and were no longer on first-line treatment. Conclusion: The TKI era has been practice changing; however, little is understood from the perspective of people living with EGFR-m NSCLC. This paper is the first to explore this and found it is possible to have people self-report complex health information about their lung cancer. In addition, although most participants were diagnosed after osimertinib became guideline-recommended treatment, disparities in treatment were identified.